(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research investigated marital relationship among Muslim Couples in Ringim Local Government Area; The Institution of marriage occupied highest position in Islam, the importance of marital relationship plays significant role within the frame work of Islam.This research investigated and provided some solution to address these issues among Muslim couples in Ringim Local Government Area. The methodology employed in the conduct of this research is ethnography of communication method which comprises the use of observation and interview as primary sources of data. More so, secondary sources of data collection such as: written literature, textbooks, journals and browsed materials on challenges of marital relationship among Muslim Couples was also used. The findings propose valued perceptions and recommendations bring into line with best practices of marital relationship, contributing to the advancement of institution of marriage among couples in the Area.